Identification of Production Process and Palm Sugar Distribution in Small and Medium Enterprises (UKM) in Napano Kusambi District, West Muna Regency - Sutantri Sutantri; La Rianda; Sakir Sakir (Jurusan Ilmu dan Teknologi Pangan, Fakultas Pertanian,, 2020)
The objectives of this study are (1). know the profile of the palm sugar industry in Napano Kosambi District, West Muna Regency. (2) know the identification of the production and marketing process of palm sugar in Napano Kosambi District, West Muna Regency. The data processed using qualitative data to identify the production process and marketing of palm sugar in small and medium enterprises (UKM) as many as 4 businesses. Data collection using the method of observation, interviews, and documentation. The channel pattern of palm sugar marketing uses a simple random sampling method. The results of this study indicate that the palm sugar processing business, the variable value of the palm sugar raw material is the total amount of business 1, II, III, and IV: 181 liters; 191 liters; 175 liters; 184 liters. The selling price of palm sugar ranges from Rp. 8,000-11,000, of which business I usually sell its products for Rp. 8,000, business II sells its products for Rp. 10,000, business III sells its products at Rp. 9,000 and business IV sells its production price at Rp. 11,000. With the total yield of palm sugar production from businesses I, II, III, and IV in West Muna District, Napano Kusambi District, around 141 seeds/month. Meanwhile, the total profit yields from the highest to the lowest, namely business IV, the highest is around Rp. 925,270 / month followed by business II amounting to Rp. 839,373 / month, followed by business I of Rp. 491,905 / month and the lowest is business III of Rp. 442,500 / month.